Pendampingan Dan Pelatihan Diversifikasi Pengolahan Ikan Bagi Ibu-Ibu Nelayan Di Pulau Sembilan Kabupaten Sinjai - DIAN SAFITRI; WIRA YUSTIKA R; IRMAWATY IRMAWATY; HILMI HAMBALI (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Community service is intended to educate or transfer knowledge from information sources to recipients of information. This program has provided changes both socially and economically with the main target being welfare. The Sembilan Island region is one of the areas located in Sinjai Regency which has considerable land and sea potential. The marine and fisheries sector in this region in the short term is known as a sector that is able to have an impact on production activities from other sectors (Output Multiplier / OM) and increase in people's income (Income Multiplier / IM). The community service program that has been carried out involves 30 fishermen mothers in Pulau Sembilan and divided into 5 small groups accompanied by tutorials. Fish is processed into various products including fish balls, fish nuggets and shredded fish. The assistance and training that has been done have increased the community's confidence in increasing their income (Income Multiplier / IM) so that they can sustain the community's economy in Sembilan Island, Sinjai Regency. Key Words: Training, Diversification, Processed Products, Fishermen